An overview of internet engineering task force mobility management protocols: approaches and its challenges - Prabha Mahenthiran; Dinakaran Muruganadam (Institute of Advanced Engineering and Science, 2022)
In recent years, internet protocol mobility management has become one of the most popular research areas in networking. Mobility management protocols are in charge of preserving continuing communications as a user roam between different networks. All existing internet protocols (IP), like MIPv6, and PMIPv6, rely on a centralized mobility anchor to control mobile node traffic and signaling. The disadvantages of centralized mobility management (CMM) include ineffectiveness in handling massive volumes of traffic, poor scalability, wasteful use of network resources, and packet delay. When CMM is required to handle mobile media, which demands a huge amount of information and frequently needs quality of services (QoS) such as session continuance and reduced latency, these difficulties become apparent. It drives the need for distributed mobility management protocol (DMM) systems to manage the growing amount of mobile data, the overwhelming of this is video communication. DMM approaches could be regarded as an innovative and effective method to deal with mobility. An overview of the CMM protocol and its drawbacks are analyzed. This study examines the various DMM protocol techniques and their performance metrics are compared to highlight similarities and differences. The study reveals the network-based DMM protocol improves overall handoff time and packet loss.